Discovery of new 5-substituted-indole-2-carboxamides as dual epidermal growth factor receptor (EGFR)/cyclin dependent kinase-2 (CDK2) inhibitors with potent antiproliferative action. Issue 4 (16th March 2023) - Mohamed, Fatma A. M.; Alakilli, Saleha Y. M.; El Azab, Eman Fawzy; Baawad, Faris A. M.; Shaaban, Esraa Ibrahim A.; Alrub, Heba Abu; Hendawy, Omnia; Gomaa, Hesham A. M.; Bakr, Adel G.; Abdelrahman, Mostafa H.; Trembleau, Laurent; Mohammed, Anber F.; et al.
Abstract : A new series of 5-substituted-3-ethylindole-2-carboxamides 5a–k and 6a–c was designed and synthesised in an attempt to develop a dual targeted antiproliferative agent. Abstract : A new series of 5-substituted-3-ethylindole-2-carboxamides 5a–k and 6a–c was designed and synthesised in an attempt to develop a dual targeted antiproliferative agent. Various spectroscopic methods of analysis were used to confirm the structures of the new compounds. The antiproliferative effect of compounds 5a–k and 6a–c against four cancer cell lines was investigated. Compounds 5a–k and 6a–c had significant antiproliferative activity against the four cancer cell lines tested, with mean GI50 values ranging from 37 nM to 193 nM. The most powerful derivatives were compounds 5g, 5i, and 5j, with GI50 values of 55 nM, 49 nM, and 37 nM, respectively, in comparison to the reference erlotinib, which had a GI50 of 33 nM. The four most potent compounds, 5c, 5g, 5i, and 5j, were then investigated for their efficacy as EGFR inhibitors, and the findings showed that the tested compounds inhibited EGFR with IC50 values ranging from 85 nM to 124 nM when compared to the reference erlotinib (IC50 = 80 nM). Moreover, compounds 5c and 5g inhibited CDK2 with IC50 values of 46 ± 05 nM and 33 ± 04 nM, respectively. The EGFR and CDK2 assays revealed that compounds 5i and 5j displayed potent antiproliferative activity and can be considered as potential dual EGFR and CDK2 inhibitors.